"Procedural Guarantees for EU Citizens against Expulsion in the Light of Directive 2004/38/EC" - Wojnowska-Radzińska, Julia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The present paper analyses the scope of protection of EU citizens against expulsion under Directive 2004/38/EC and in the case-law of the Court of Justice of the Eu-ropean Union. According to the provision of this Directive, an EU citizen threatened with expulsion must have access to relevant documents and accessible information on the legal procedures to be followed in his/her case. Even if the government claims that national security interests keep courts from disclosing the evidence to the EU citizen, it is obliged to submit any material or evidence capable of corroborating that the interests of national security or public order are at stake. The CJEU requires that the evidence has to be scrutinised by the adversarial proceedings. In particular, the EU citizen must be informed, in any event, of the essence of the grounds on which an expulsion decision is based, as the necessary protection of State security cannot have the effect of denying the person concerned of his/her right to be heard.